A new genus and species of larval mites (Acari: Prostigmata: Microtrombidiidae) from Iran - Sedghi, Ali; Saboori, Alireza; Akrami, Mohammad Ali; Hakimitabar, Masoud (Zootaxa, 2010)
Persianthrombium farajii Sedghi, Saboori & Hakimitabar gen. et sp. nov. (Acari: Microtrombidiidae) is described and illustrated from larvae ectoparasitic on undetermined Locusta (Orthoptera: Acrididae) from Jahrom, Fars Province, Iran. A key to larval genera of Microtrombidiidae with three dorsal scuta is presented.